Genetic Polymorphisms in microRNA Genes Targeting PI3K/Akt Signal Pathway Modulate Cervical Cancer Susceptibility in a Chinese Population - Chen, Kerong; Yan, Zhiling; Dong, Xudong; Liang, Yan; Yao, Yueting; Zhang, Shao; Liu, Weipeng; Li, Chuanyin; Yao, Yufeng; Shi, Li (Frontiers in Genetics, 2022)
Polymorphisms in miRNA genes could influence the expression of miRNAs that regulate the PI3K/Akt signalling pathway and play crucial roles in cancer susceptibility. To investigate the association of single nucleotide polymorphisms (SNPs) in miRNA genes of PI3K/Akt with cervical intraepithelial neoplasia (CIN) and CC, nine SNPs located in miRNA genes were selected for genotyping, and the association of these SNPs with CIN and CC risk was evaluated. A total of 1402 participants were enrolled in the current study, including 698 healthy individuals in the control group, 431 patients with CC, and 273 patients with CIN. Nine SNPs in miRNA genes (rs107822 in miR-219a, rs10877887 in let-7i, rs2292832 in miR-149, rs353293 in miR-143, rs3746444 in miR-499, rs3803808 in miR-132, rs4078756 in miR-10b, rs629367 in let-7a, and rs7372209 in miR-26a) were genotyped using MassArray, and the association of these SNPs with CIN and CC were analysed. The results showed that the frequencies of rs107822 in miR-219a and rs2292832 in miR-149 were significantly different between the control and CC groups (P<0.005). The C allele of rs107822 in miR-219a was associated with an increased risk of CC (OR=1.292, 95%CI:1.088-1.536) whereas the C allele of rs2292832 in miR-149 was associated with a decreased risk of CC (OR=0.767, 95%CI:0.639-0.921). The results of inheritance model analysis showed that the best-fit inheritance models for rs107822 and rs2292832 were log-additive. The 2CC+CT genotype of rs107822 could be a risk factor for CC when compared with the TT genotype (OR=1.28, 95%CI:1.08-1.51). The 2CC+CT genotype of rs2292832 could be a protective factor against CC when compared with the TT genotype (OR=0.76, 95%CI:0.64-0.92). Our results suggest that rs107822 in the promoter region of miR-219a and rs2292832 in pre-miR-149 region are associated with the risk of CC.